Risk Factors for Sleep-Disordered Breathing in Pregnancy - Pien, Grace W. (Thorax, 2013)
RATIONALE: Symptoms of sleep-disordered breathing (SDB) are common among pregnant women, and several studies link SDB symptoms with gestational hypertension and preeclampsia. However, few prospective studies objectively measuring SDB during pregnancy have been performed. OBJECTIVES: We performed a prospective cohort study examining risk factors for third trimester SDB in pregnant women. MEASUREMENTS AND METHODS: 105 pregnant women from the Hospital of the University of Pennsylvania obstetrics practices completed first and third trimester overnight polysomnography studies. We examined whether the number of sleep-disordered breathing events per hour of sleep increased during pregnancy. We performed unadjusted and multivariable logistic regression analyses to estimate the effects of usual and pregnancy-specific characteristics on development of third trimester OSA. In secondary analyses, we examined the relationship between objectively measured SDB, hypertensive disorders of pregnancy, and other adverse maternal-fetal outcomes. MAIN RESULTS: Mean AHI increased from 2.07 (SD 3.01) events/hour at baseline (first trimester) to 3.74 (SD 5.97) in the third trimester (p=0.009). 10.5% of women had OSA in the first trimester. By the third trimester, 26.7% of women had OSA. In multivariable analyses, first trimester BMI and maternal age were significantly associated with third trimester OSA. CONCLUSIONS: Third trimester OSA is common. Risk factors for third trimester OSA among women without baseline SDB include higher baseline BMI and maternal age.